Inhibiting CB1 receptors improves lipogenesis in an in vitro non-alcoholic fatty liver disease model - Shi, Dongmei (Lipids Health Dis, 2014)
BACKGROUND: The endocannabinoids system (ECs) mediated mainly by CB1 and CB2 receptors plays an important role in non-alcoholic fatty liver disease by regulating lipid metabolism. This study is to further investigate the expression of CB1 and CB2 in the fat accumulation liver cells and to identify possible underlying mechanism by detecting the key lipogenesis factors. METHODS: Sodium oleate and sodium palmitate were added into the HepG2 cell line for forming fat accumulation liver cell. MTT assay was used to test the cell’s cytotoxicity. The accumulation rate of fat in HepG2 cell was analyzed by the fluorescent staining. The mRNA and protein expression levels of CB1, CB2, SREBP-1c, ChREBP, L-PK, ACC1, FAS, LXRs and RXR were detected by RT-PCR and Western blot before and after the use of the antagonist. RESULTS: The receptors of CB1 were expressed in HepG2 cells with low levels while in HepG2 fatty liver cells with higher levels (p < 0.05). However, after the application of antagonist, the expressions were significantly decreased (p < 0.05). The expressions of SREBP-1c, ChREBP and LXRs were detectable in HepG2 cells and the expressions were increased in HepG2 fatty liver cells (p < 0.05). After using the antagonists, the expressions of SREBP-1c, ChREBP, LXRs, ACC1 and FAS were significantly decreased (p < 0.05). But L-PK and RXR changed little in two groups (p > 0.05). CONCLUSION: Results of the present study demonstrated that CB1 receptors had important pathophysiological effects on the formation of fatty liver. CB1 receptors could be regulated by SREBP-1c, ChREBP and LXRs. Therefore, targeting CB1 receptors for the treatment of NAFLD might have a potential application value.